Nivel de ventas de la Empresa “Agrileve S.A.” de la ciudad de Babahoyo. - Sánchez Moran, Lisbeth Cecilia (2022)
The case study entitled "Sales level of the company "AGRILEVE S.A" of the city of Babahoyo, as a commercial point that is dedicated to the commercialization of various machinery, services, products and agricultural inputs. Its general objective is to analyze the level of sales of the company Agrileve S.A. of the city of Babahoyo, through a situational diagnosis for its positioning in the local market, the descriptive method and techniques such as: Survey and interview were applied, concluding the following: The study is framed under the guidelines established by the Technical University of Babahoyo with which it has been tried to establish and know the problems raised in the company "AGRILEVE S.A" that lacks effective sales and advertising strategies to retain customers with their products. and services, so this generates a negative effect for the company since it runs the risk of losing fixed customers due to the different factors that have been studied in this present case study. It is like a common logic, that a company without sales runs the risk of definitive closure. These and other negative peculiarities that affect the company are detailed in greater depth in the development of this study.